Towards a Sustainable Value Co-Creation Framework: Ethical Cognitive Couture, Cognitive System, and Sustainability - Prafulla Kumar Padhi (International Journal of Engineering and Management Research, 2018)
The aim of this paper is to develop a sustainable value co-creation (SVCC) conceptual framework in which ethical cognitive couture (ECC) brand stakeholders co-create value for sustainability facilitated by cognitive system and ethical criteria compliance. As per most literature on service dominant logic (SDL) perspective, all providers are service providers, and service is the fundamental basis of exchange. Even though SDL paradigm has contributed to the conceptualization of “value co-creation”, so far, no academic research study has investigated the role played by the stakeholders in ECC products and services sustainability. Sustainable value co-creation (SVCC) - a business strategy focused on inscribing economic, socio-cultural and environmental issues by recognizing sustainable competitive advantage that bring about community benefit. The research methodology utilizes literature review, relevant databases analytics, and multiple case studies that facilitates broad keywords search, identify high quality peer reviewed papers to obtain perspective on ECC brands to conceptualize a SVCC framework. The contribution of this study provides valuable insights, for the first-time, bestowing new knowledge to the literature on sustainable value co-creation (SVCC) framework elaborating systematically the five building blocks - Risk, Exchange, Advantage, Communication, and Transparency (REACT) and practices adopted by the stakeholders for the ECC market. This comprehensive framework can serve as an education model and practice guide for academia, industry practitioners, policy makers and non-profit organizations.